Estudio de mercado para la exportación de la Malanga en la Novena Región de Temuco- Chile - Corella Erazo, María Belén (2012)
Considering that Ecuador is an agricultural country and making reference that this sector contribute to Ecuadorian’s economy .The new tendency go through products that reduce the use of chemical products and low prices of production. It is too necessary to make a study about market in order to export and distribute malanga to Chilean market in the IX Temuco’s Region.´ We made as an investigation instrument a descriptive studio in order to punctualize the process of commercialization of malanga from the gathering to the prima matter to its distribution...